PENGARUH KURANGNYA MENERAPKAN PENGGUNAN TEKNOLOGI TERHADAP MOTIVASI BELAJAR SISWA - Lutfia Athayati Falny; Shafirza Azzahra Pohan; Nadila Salsabila; Lam Nur Andayani; Nurul Khoiriah Ritonga; Arnita Synctiana Sari; Rizka Zahara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to analyze the influence of the lack of application of technology in learning on elementary school students' learning motivation. A qualitative approach is used with descriptive methods to explore student and teacher experiences, identify barriers to implementing technology, and have an impact on student learning motivation. Data was obtained through direct observation in class involving 15 students and a teacher as participants. The research results show that the majority of students rarely use technology in learning, resulting in low learning motivation due to monotonous teaching methods. The main obstacles found include limited technological facilities, minimal teacher training, and lack of time to integrate technology into the curriculum. The use of technology has been proven to provide significant benefits, such as increasing learning interactivity, enriching the learning experience, and encouraging active student involvement. This research concludes that the application of technology in learning needs to be supported by various parties through the provision of adequate infrastructure, teacher training, and supportive educational policies.